Muslims in the Canadian Mosaic (American Journal of Islam and Society, 1992)
Almost one-third of the total population of Muslims in the worldtoday lives as a "minority" in lands where people of other faiths,cTeeds and ideologies have administrative, political and legislativecontrol. As a religious minority, these Muslims face certain difficultiesand challenges in practising their own distinct way of life.'This paper, based on a study of the Muslim community in theCanadian National Capital Region (CNCR) conducted in 1992, exploreshow the Muslim community in the CNCR has integrated itself intoCanadian society and how it has sought to maintain its Islamic identityin terms of religious practice and belief. It will demonstrate the impact ofCanadian social values and structure on the formation of the Islamicidentity of Muslims living in Canada and will also examine some of theways by which this identity is maintained. This will be achieved byexamining previous work in the field, the sociohistorical development andsocio-demographic characteristics of the Muslim community in Canada(in particular in the CNCR), and immigration factors. The methodologyand techniques used, findings, and conclusions will also be discussed.Previous Work in the FieldTo date, there have been few studies on North American Muslimcommunities. Those that do exist have focused primarily on the MiddleEastern (i.e., Arab) communities in Canada and the United States. Manyhave discussed the processes of acculturation and assimilation, in additionto attempts to preserve the traditional values, of these communities. Theresults have indicated a negative correlation between Islamic observanceand non-Islamic societies. Since previous inquiries did not focus on the ...